Underwater Crowd Flow Detection Using Lagrangian Dynamics - Soori, Umair; Arshad, Mohammad Rizal (2008)
Group movement is the most important tool to study the animal behaviours, which allow animals to respond their condition with respect to environment. Crowd flow in underwater scene is used to study fish schooling characteristics.